Integration of encapsulated cells on microfluidic systems for the generation and delivery of specific biomarker profiles - Monge, R.; Sáenz del Burgo, L.; Llamazares, G.A.; Movilla, N.; Ochoa, I.; Santos, E.; Hernández, R.M.; Orive, G.; Pedraz, J.L.; Fernández, L.J. (Jornada de Jóvenes Investigadores del I3A, 2014)
This work presents the design and fabrication of a SU-8 based microfluidic chip for encapsulated myoblasts, a complete microfluidic setup for long term cell culture, together with the first profile secretion analysis results.